2016
DOI: 10.1681/asn.2015050535
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Major Hemorrhage with CKD

Abstract: New staging systems for CKD account for both reduced eGFR and albuminuria; whether each measure associates with greater risk of hemorrhage is unclear. In this retrospective cohort study (2002-2010), we grouped 516,197 adults ≥40 years old by eGFR (≥90, 60 to <90, 45 to <60, 30 to <45, 15 to <30, or <15 ml/min per 1.73 m(2)) and urine albumin-to-creatinine ratio (ACR; >300, 30-300, or <30 mg/g) to examine incidence of hemorrhage. The 3-year cumulative incidence of hemorrhage increased 20-fold across declining e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 45 publications
(62 reference statements)
3
99
0
9
Order By: Relevance
“…As previously described, hemorrhage risk scores in patients with atrial fibrillation include kidney dysfunction as a dichotomous risk factor, whereby dialysis patients are treated the same as patients with less severe kidney dysfunction. This would result in a considerable underestimate of hemorrhage risk when applied to dialysis patients, as this risk increases in an exponential fashion with declining eGFR …”
Section: Hemorrhage Risk Assessment In Atrial Fibrillationmentioning
confidence: 99%
“…As previously described, hemorrhage risk scores in patients with atrial fibrillation include kidney dysfunction as a dichotomous risk factor, whereby dialysis patients are treated the same as patients with less severe kidney dysfunction. This would result in a considerable underestimate of hemorrhage risk when applied to dialysis patients, as this risk increases in an exponential fashion with declining eGFR …”
Section: Hemorrhage Risk Assessment In Atrial Fibrillationmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a common condition in the community , and is independently associated with increased risk of bleeding in operative and nonoperative settings . Gastrointestinal (GI) bleeding is the most common manifestation of bleeding .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CKD showed increased rates of CD (6.5% vs. 2.9%, P = 0.007), MACEs (26.9% vs. 14.0%, P < 0.001), stroke (5.2% vs. 2.8%, P = 0.04), and major bleeding (7.0% vs. 2.9%, P = 0.001) compared to those without CKD during follow‐up (Table ; Figures B,E and A,B). The mechanism underlying the relationship between renal function and adverse events is not clearly understood, but patients with CKD have comorbidities of cardiovascular risk factors and major bleeding . The effect of CKD on lipids and increased calcification may contribute to neoatherosclerosis and cardiovascular mortality .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying the relationship between renal function and adverse events is not clearly understood, but patients with CKD have comorbidities of cardiovascular risk factors and major bleeding. [26][27][28][29] The effect of CKD on lipids and increased calcification may contribute to neoatherosclerosis and cardiovascular mortality. 30,31 Kurihara et al showed that TLR at 2-4 years was predicted by patient characteristics, which could be interpreted as factors strongly related to neoatherosclerosis.…”
Section: Relationship Between Ckd and Clinical Outcomesmentioning
confidence: 99%